Uncovering Prolonged Grief Reactions Subsequent to a Reproductive Loss: Implications for the Primary Care Provider - Grauerholz, Kathryn R.; Berry, Shandeigh N.; Capuano, Rebecca M.; Early, Jillian M. (Frontiers in Psychology, 2021)
Introduction There is a paucity of clinical guidelines for the routine assessment of maladaptive reproductive grief reactions in outpatient primary care and OB-GYN settings in the United States. Because of the disenfranchised nature of perinatal grief reactions, many clinicians may be apt to miss or dismiss a grief reaction that was not identified in the perinatal period. A significant number of those experiencing a reproductive loss exhibit signs of anxiety, depression, or post-traumatic stress disorder. Reproductive losses are typically screened for and recorded numerically as part of a woman’s well-visit intake, yet this process often fails to identify patients emotionally troubled by a prior pregnancy loss. Methods A summative content analysis of 164 recent website blogs from female participants who self-reported having experienced a miscarriage or abortion in their lifetime was conducted. The narratives were reviewed for details regarding the time span between the pregnancy loss and the composition of the blog post. The stories were analyzed for subsequent relationship problems and detrimental mental health conditions. Maladaptive reactions were contrasted for those that indicated a greater than 12 months’ time-lapse and those who had not. Results More than a third (39.6%) of the women reported in the narrative that at least one year or more had passed since experiencing the miscarriage or abortion. For those women, the median time span between the loss and composing the blog was 5 years with a range of 47 years. There was a two-fold increase in reported maladaptive grief reactions by those who indicated writing about their abortion or miscarriage more than a year later. Mental health conditions attributed to the reproductive loss by those who reported longer bereavement times included subsequent relationship problems, substance misuse, depression, suicidal ideation, and PTSD. Discussion Grief reactions following the loss of a pregnancy may be prolonged or delayed for several months which can contribute to adverse biopsychosocial outcomes. Recognition and treatment of maladaptive grief reactions following a pregnancy loss are critical. Screening methods should be enhanced for clinicians in medical office settings to help identify and expedite the appropriate mental health assistance.